Clinical and pathomorphological analysis of deaths from COVID-19 in 2020 - O. V. Riabokon; L. M. Tumanska; V. V. Cherkaskyi; Yu. Yu. Riabokon (Patologìâ)
The aim of the work – to conduct clinical and pathomorphological analysis of deaths from COVID-19 in 2020.